2022
DOI: 10.1186/s12889-022-12948-w
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and individual factors associated with gestational weight gain

Abstract: Background Environmental factors have an impact on inappropriate food choices and sedentary lifestyle, and both individually and in combination these factors favour improper gestational weight gain (GWG) and consequent maternal and neonatal health problems. The objective of this study was to analyze the environmental and individual factors associated with GWG. Methods Data were from “Born in Belo Horizonte: Survey on childbirth and birth”, a hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…Sufficient income and easy access to low-fat food enabled women to purchase nutritious food and practice a healthy diet for weight control. Previous evidence also showed that access to healthy food [ 8 , 50 ] and sufficient income [ 11 ] are facilitators of adequate GWG. However, easy access to healthy food as low-fat food was also significantly associated with excessive GWG.…”
Section: Discussionmentioning
confidence: 99%
“…Sufficient income and easy access to low-fat food enabled women to purchase nutritious food and practice a healthy diet for weight control. Previous evidence also showed that access to healthy food [ 8 , 50 ] and sufficient income [ 11 ] are facilitators of adequate GWG. However, easy access to healthy food as low-fat food was also significantly associated with excessive GWG.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, low and middle-income countries have reported a higher prevalence of inadequate GWG than excessive [13,15,16,[47][48][49]. Excessive GWG is an emerging maternal health issue in transiting economies with increased adverse perinatal outcomes such as macrosomia, increased operative delivery, postpartum weight retention, and maternal obesity in the subsequent pregnancies and future risk of non-communicable diseases [7,10,24,25,[50][51][52].…”
Section: Plos Onementioning
confidence: 99%
“…A medical records review revealed that individuals living in food deserts were more likely to have at least one morbidity during pregnancy versus those who did not (adjusted OR 1.64; 95% CI [1.18, 2.29]) 72 . A study conducted in Brazil revealed excessive gestational weight gain was associated with the number of food‐purchasing establishments near an individual's place of residence, 73 and another study found that gestational diabetes mellitus (GDM) was less likely for women living in areas with better access to healthier foods. Furthermore, these women were less likely to require medication to control GDM or to deliver an infant with macrosomia 74 .…”
Section: Introductionmentioning
confidence: 99%